Parental Perceptions of The Need for Sexual and Reproductive Health Education for Early Adolescents - Rery Kurniawati Danu Iswanto; Zahroh Shaluhiyah; Bagoes Widjanarko; Cahya Tri Purnami (Public Health of Indonesia, 2026)
Background: The urgency of reproductive health education for adolescents has been intensified by challenges such as early puberty and exposure to digital media in an era characterized by unrestricted access to information and shifting societal norms. The role of parents as primary educators is critical to ensuring a healthy transition from adolescence to adulthood. However, significant barriers are encountered by parents, particularly those with limited education and digital literacy, in fulfilling this role. Objective: The objective of this study is to analyze parental perspectives regarding reproductive health needs as a foundation for developing a model to enhance their capacity in educating early adolescents. Methods: This study used a sequential explanatory mixed-methods design in rural Indonesia. A survey of 106 parents of early adolescents (aged 10–12) was followed by in-depth interviews with 9 purposively selected participants. Quantitative data were analyzed descriptively using SPSS, while qualitative data underwent thematic analysis using ATLAS.ti to explore communication patterns and parental needs related to adolescent reproductive health. Results: Thematic analysis revealed seven key themes: (1) basic understanding of adolescent reproductive health, (2) education on values and norms, (3) parental concerns regarding external challenges, (4) dynamics of parent-child communication, (5) communication barriers, (6) the role of parents as shaped by gender, and (7) needs for specific materials, methods, and media. A strong emphasis was placed by parents on the need for information regarding puberty, strategies for effective communication, and approaches to engaging with adolescents. School-based counseling and face-to-face sessions were identified as effective delivery methods, with preferences expressed for media such as books and WhatsApp groups. Conclusion: Efforts to provide reproductive health education by parents have been shaped by limited knowledge, perceptions of taboo, and external influences. Programs designed to address these challenges must be tailored to meet the specific needs of parents. The activation of parent associations in schools has been identified as a promising approach to disseminate information and strengthen reproductive health education. Keywords: parents' perspectives; reproductive health education; early adolescents